Computational activation of CISD3 by a novel flavonoid compound for cardiac ageing and cardiovascular health - Javed Iqbal Wattoo; Kaniz Fatima; Abdur-Rehman Munir; Mahnoor Abid (Scientific Reports, 2026)
Abstract CISD proteins, members of the CDGSH iron-sulfur domain family, include CISD1, CISD2, and CISD3, which are associated with age-related disorders and mitochondrial dysfunction. CISD3, characterised by a 2Fe–2 S cluster and localized in the outer mitochondrial membrane, plays a critical role in mitochondrial homeostasis. A decline in CISD3 levels with age may accelerate cardiac ageing by inducing mitochondrial dysfunction, impaired autophagy, proteotoxic stress, disrupted nutrient signalling, cellular senescence, and oxidative stress, ultimately leading to apoptosis. CISD3 deficiency also triggers endoplasmic reticulum stress, disrupts calcium regulation, and diminishes oxidative phosphorylation, contributing to cardiovascular pathologies such as cardiac hypertrophy, ischemia, and heart failure. Using a computational drug discovery approach, this study identifies (2r)-2-[3,4-Bis(Oxidanyl)phenyl]-6-Oxidanyl-2,3-Dihydrochromen-4-One as a potential CISD3 activator. Docking simulations reveal its strong binding affinity and predicted therapeutic effects in mitigating metabolic dysfunction. In high-fat diet models, the compound reduces total cholesterol, limits aortic inflammation and fibrosis, regulates endothelial function, and inhibits foam cell formation via the LXRα pathway. It also alleviates oxidative stress, enhances antioxidant capacity, and improves myocardial function through the Nrf2/ARE pathway. These findings suggest CISD3 activation as a promising strategy for preserving cardiovascular health and delaying cardiac ageing.